Trends in fungal colonization of pancreatic necrosis in patients undergoing necrosectomy for acute pancreatitis - King, N. K. K. (2005)
Background. This study examines fungal colonization of post-inflammatory pancreatic necrosis in a cohort of patients undergoing open surgical necrosectomy in a single, tertiary referral unit over a 10-year period. Methods. The charts of all patients with acute pancreatitis who underwent surgical necrosectomy during the period January 1992 to December 2001 were examined. Following exclusions a population of 30 patients were identified. There were 18 men with a median (range) age of 42 (20–69) years. Sixteen (53%) underwent surgery because of positive fine needle aspirates and the remainder underwent surgery on clinical grounds. Twenty-nine (97%) received antibiotics prior to necrosectomy. Principal outcomes were the results of microbiological culture with reference to isolation of fungi, site of isolates, trends in colonization and outcome. Results. Candida were cultured from pancreatic necrosis in 5 (17%). These 5 individuals also had positive candidal cultures from sputum or bronchial aspirates. There were no deaths in patients with fungal colonization of necrosis. There was no change in the annual incidence of fungal colonization of necrosis over the study period. Conclusion. Although this is a small study, there are two consistent observations: mortality in fungal colonization of necrosis was low and there was no change in the annual incidence of fungal colonization of necrosis over the decade. Discrepancies between these findings and those of previous reports mandate larger prospective evaluation.